2023
DOI: 10.5187/jast.2023.e6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for improving meat protein digestibility in older adults

Abstract: Writing -review & editing: Hur SJ, Lee SY. Ethics approval and consent to participateThis article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…Tis improvement can be attributed to enhanced digestion and mineral uptake mechanisms. Te ultrasonication treatment likely breaks down protein structures into smaller peptides, allowing for better access to mineral binding sites and facilitating the formation of soluble zincchickpea protein complexes [107]. Consequently, more zinc ions are released from the bound complexes during digestion, making them available for absorption in the digestive tract.…”
Section: Mineral Bioavailabilitymentioning
confidence: 99%
“…However, it has been found that the protease activity in papayas of different origins can vary significantly due to its different concentrations, necessitating careful selection of raw materials and papain sources [6]. Enzyme preparations with papain are recommended to improve food digestion, but papain only has proteolytic activity and requires supplementation with other enzymes [7].…”
Section: Main Partmentioning
confidence: 99%
“…A comparative analysis of actinidin with bromelain and papain revealed significant differences in protease activity against animal-derived proteins, depending on whether connective tissue or muscle protein was used as a substrate [6,7]. When comparing the activity of cysteine proteases, it was found that actinidin and bromelain are particularly effective for collagen hydrolysis [7].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation